2012
DOI: 10.1371/journal.pntd.0001904
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Temperature-Switch PCR-Based SNP Typing Method for Mycobacterium ulcerans

Abstract: Mycobacterium ulcerans (M. ulcerans), the causative agent of the devastating skin disease Buruli ulcer (BU), is characterized by an extremely low level of genetic diversity. Recently, we have reported the first discrimination of closely related M. ulcerans variants in the BU endemic Densu River Valley of Ghana. In the study real-time PCR-based single nucleotide polymorphism (SNP) typing at 89 predefined loci revealed the presence of ten M. ulcerans haplotypes circulating in the BU endemic region. Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…ulcerans is the close correlation between genotype and the geographic origin of a strain, but its restricted genetic diversity has limited the application of traditional molecular epidemiological methods such as VNTR-typing to discriminate between isolates at the village or even regional scales. The advent of low cost genomics has opened up new possibilities to explore and track the movement and spread of this pathogen within communities [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…ulcerans is the close correlation between genotype and the geographic origin of a strain, but its restricted genetic diversity has limited the application of traditional molecular epidemiological methods such as VNTR-typing to discriminate between isolates at the village or even regional scales. The advent of low cost genomics has opened up new possibilities to explore and track the movement and spread of this pathogen within communities [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of a case-control study carried out in a BU endemic region of south-eastern Australia indicated reduced odds of having BU for individuals who frequently used insect repellent and increased odds for those who were bitten by mosquitoes [21] . In African BU endemic settings, the highly focal transmission of M. ulcerans haplotypes [12] , [22] , [23] , as well as the distribution pattern of BU lesions on the body [11] , speak against an exclusive role of mosquito vectors in transmission. Here we observed in children <5 years frequent sero-conversion for the MSP-1 antigen of the mosquito-transmitted malaria parasites in the absence of an IgG response against the M. ulcerans 18 kDa shsp.…”
Section: Discussionmentioning
confidence: 99%
“…SNP typing has shown greater strain discrimination among M. ulcerans than VNTR typing [10] , [11] but has not yet been successfully used on patient samples or environmental samples. Results presented here support the importance of developing finer molecular tools for identification of M. ulcerans as well as the importance of including a 25°C incubation temperature for improving isolation of pathogenic mycobacterial species from patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic data from a number of strains from Ghana has facilitated the development of methods based on the detection of single nucleotide polymorphisms (SNP typing) for studying M. ulcerans transmission pathways and phylogenetic relationships [10] , [11] . However, these methods have only been used successfully with pure bacterial cultures [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%